Rehabilitation of Women with Stress Urinary Incontinence: A Case Report - Khatun, Iren; Islam, Waliul (Archives of Clinical and Medical Case Reports, 2022)
Introduction: Urinary incontinence can be evident in women, after multiple child birth or with increasing age. The nonsurgical management is considered as the first line of management, the preliminary management of simple SUI includes a variety of noninvasive interventions, including behavioral modification, Pelvic Floor Exercises (PFEs) with or without biofeedback, and other accessory teaching aids. Case Report: The purpose of the present study is to find out if repetition of pelvic stabilization exercise impacts upon the management of stress urinary incontinence. For the management of Urinary incontinence, she has been treated by A Bangla booklet on urinary incontinence, Kegal exercises and pelvic floor exercises in a booklet instruction in Bangla, an exercise log book to maintain exercise. All the pelvic floor exercise started by 10 repetitions of exercise each, increasing 10% of exercise in each week for 4 weeks duration. After 4 weeks clinically significant improvements found in strength and endurance of pelvic floor muscles and ICIQ- UI questionnaire (brief). Conclusion: Stress urinary incontinence can degrade patient’s physical, functional and daily living status. Structured exercise therapy determined by physiotherapists contributes to the improvement of muscle function, function of genito-urinary system and quality of life for these patients.